2009
DOI: 10.1016/j.jjcc.2008.06.007
|View full text |Cite
|
Sign up to set email alerts
|

MRSA tricuspid valve infective endocarditis with multiple embolic lung abscesses treated by combination therapy of vancomycin, rifampicin, and sulfamethoxazole/trimethoprim

Abstract: A 26-year-old pregnant woman who was an intravenous drug user (IDU) was admitted to our hospital for the treatment of tricuspid valve infective endocarditis (IE) and lung abscesses due to methicillin-resistant Staphylococcus aureus (MRSA). We started to treat her with vancomycin (VCM) alone and then in combination with rifampicin (RFP), but her condition did not improve. Then we added sulfamethoxazole/trimethoprim (SMZ/TMP) to VCM and RFP. After that, she improved rapidly. In Japan, there are very few reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The impact of cardiovascular complications, such as valvular damage, cardiac abscess, conduction abnormalities, and stroke on IE outcomes are well-studied [1][2][3][4][5]. However, a recent literature search regarding the effect and management of pulmonary complications (empyema, lung abscesses, and septic pulmonary emboli) on outcomes of IE consists mainly of case reports [6][7][8][9][10][11][12][13][14][15]. There are no large scale epidemiological, retrospective, or prospective studies on the subject and the epidemiology of IE-PC is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of cardiovascular complications, such as valvular damage, cardiac abscess, conduction abnormalities, and stroke on IE outcomes are well-studied [1][2][3][4][5]. However, a recent literature search regarding the effect and management of pulmonary complications (empyema, lung abscesses, and septic pulmonary emboli) on outcomes of IE consists mainly of case reports [6][7][8][9][10][11][12][13][14][15]. There are no large scale epidemiological, retrospective, or prospective studies on the subject and the epidemiology of IE-PC is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nemoto et al reported that MRSA prosthetic arthritis was successfully treated with a combination of vancomycin and rifampicin for 17 weeks, followed by sulfamethoxazole/trimethoprim [46]. Fujino et al also reported a case of MRSA tricuspid valve infective endocarditis treated with combination therapy [47]. In this study, 12 patients (2.2%) were infected with either MRSA or MRSE.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 51%
“…A few cases of recurrent pulmonary abscesses and empyema have been reported in the literature 3 8–10. Moreover, there are even fewer documented cases of resultant bronchopleural fistula in the literature 6 11.…”
Section: Discussionmentioning
confidence: 99%